Repellent Effectiveness of Permot Leaf Ethanol Extract (Passiflora Foetida Linn.) against Aedes Aegypti Adult Mosquitoes - David Mohamad Qadafi; Poedji Hastutiek; Lilik Maslachah; Endang Suprihati; Muhammad Hambal (Journal of Parasite Science)
Indonesia is one of the largest tropical countries in the world and various diseases can arise in the tropics which are caused by animals as vectors. An example of a vector that can carry diseases is a mosquito. Mosquitoes are insects that live side by side with humans buy act as vectors of disease. Mosquito Aedes aegypti is a type of mosquito that can carry the virus that causes Dengue Hemorrhagic Fever. This research was conducted to determine the effectiveness of Permot leaf ethanol extract (Passiflora foetida L.) as an alternative repellent against adult mosquitoes Aedes aegypti. This research was conducted from October to December 2020 and used Permot leaf ethanol extract consisting of 3 cream concentrations, namely 2.5%, 5%, 7.5%, negative control using cream without permot leaf ethanol extract and positive control using mosquito cream. The data of this study were tested using one way ANOVA to find the effectiveness rate and comparations of the each Permot leaf repellent extract. This study proven that the permot leaf ethanol extract is effective as a repellent for Aedes aegypti mosquitoes.